(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2022)
This research was conducted at As’adiyah High School Makassar. The aim was to find out the process of applying the dictation method and its difficulties in Arabic writing skills for 11th grade students of As’adiyah High School Makassar. This research is a simple qualitative and quantitative descriptive analysis research. Data were collected by means of observation, interviews, documentation and questionnaires. The data collected was analyzed by means of reduction, data presentation and verification or drawing conclusions. The results showed, (1) the application of the dictation method to the writing skills of 11th grade students of As’adiyah High School Makassar, a) before learning the teacher explained the hijaiyah letters that could be connected and not spliced; b) the implementation of dictation carried out was dictation masmu’; c) after the dictation, the teacher corrects and shows the correct writing, d) the responses given by the students regarding learning to use the dictation method in the classroom show the effect of the dictation method on improving students’ Arabic writing skills. (2) Difficulty in applying the dictation method to students’ writing abilities a) lack of allocation of learning time given during class learning; b) lack of student attention during the learning process; c) lack of student interest in learning; d) students not yet able to write Arabic with spliced ​​letters; e) students have not been able to distinguish the pronunciation of similar hijaiyah letters; f) students are still lacking in listening to Arabic reading well.